DESAIN PETA SISTEM IRIGASI TANAMAN PADI SAWAH (ORYZA SATIVA L.) DI DESA BUSISINGO KECAMATAN SANGKUB KABUPATEN BOLAANG MONGONDOW UTARA - Indry E, Karundeng; Johannes E.X. Rogi; David P. Rumambi (Universitas Sam Ratulangi, 2021)
ABSTRACTThe objectives of this study are 1). Calculate the flow rate of water. 2).Calculate the value of infiltration, percolation, evaporation and evapotranspiration.3). Make an irrigation design map for rice fields. This study uses direct datacollection methods in the field and uses secondary data. Collecting data directly inthe field and using secondary data. The results showed that based on secondarycalculation data, the water discharge value in December was 60.00 m3/second,January 97.5 m3/second and February 95.00 m3/second. Based on the data obtained,the average water loss due to infiltration is 9.64 cm/hour = 2.31 mm/day, percolationis 3.0 mm/hour = 71.9 mm/day and evaporation is 5.78 mm/day. To design anirrigation system, the effective water requirement for irrigating rice fields with anarea of approximately 50ha by reducing the initial water discharge with water lossdue to infiltration, percolation and evaporation by looking at the reference to existingdata, the results obtained are 37.88 m3/second to irrigate the land.Keywords: Irrigation, Map Design of Irrigation System